Evaluation for equity: reclaiming evaluation by striving towards counter-hegemonic democratic practices. (3rd July 2022) - Gordon, Rhyall Barry; Lumb, Matt; Bunn, Matthew; Burke, Penny Jane
ABSTRACT : Formal evaluation of policies, programmes and people has become ubiquitous in contemporary western contexts. This is the case for equity and widening participation (WP) agendas in higher education, for which evaluation is often required to measure 'what works'. Although evaluation has a 'fundamentally social, political, and value-oriented character' (Guba and Lincoln. 1989. Fourth Generation Evaluation . Newbury Park, CA: Sage, 7), an experimental approach, situated within hegemonic positivist epistemologies, has tended to prevail. In this paper, we argue that it is misguided to pursue evaluation with an apolitical pretext of independence and objectivity. Drawing on Butler's concept of performativity, we explore how hegemonic anti-democratic evaluation practices can potentially re-inscribe and reproduce the very inequalities that WP seeks to address. By critiquing the technologies of evaluation, we lay out one way of understanding how democratic evaluation practices can reclaim evaluation to make possible more diverse and socially just worlds.